The association between alteration of maternal lipid levels and birthweight at term: A within-family comparison - Chen, Qinqing; Chen, Huiqi; Wang, Minmin; Qiu, Liping; Xi, Fangfang; Jiang, Ying; Lv, Min; Huang, He-Feng; Luo, Qiong (Frontiers in Endocrinology, 2022)
Context Maternal lipid levels affect birthweight and the long-term health of the offsprings. However, this association could be influenced by genetic and other common factors. Objective This work aimed to explore the relationship between maternal lipid levels and birthweight of two pregnancies in the same mother. Methods In this population-based cohort study, 705 women and their 1 410 offsprings were included. From an initial sample of women with more than one singleton birth in the database, we made the following exclusions: missing data for pre-pregnancy BMI, pregnancy weight gain, birthweight and lipid values; maternal age less than 19 or older than 44 years old; gestational age < 37 weeks or > 41weeks, gestational diabetes mellitus/diabetic. In the second and third trimesters, serum samples were collected for the determination of fasting total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels. Then we assessed the association between maternal lipids and birthweight. Results Infants of women whose 2nd-trimester TC increased by 10th-20th percentile (-0.92~-0.56 mmol/L) from 1st to 2nd pregnancy were 239.69 (62.32~417.06) g lighter at birth than were infants of women those of 40th-50th percentile (-0.20~-0.03 mmol/L). Parity, gestational age, neonatal gender, maternal pre-pregnancy body mass index, maternal weight gain, and 3rd-trimester TC and HDL-C were all associated with higher birth weight. Every unit increase in TC in the third trimester increases birthweight by 53.13 (14.32 ~91.94) g. Conclusion Maternal TC level is associated with birthweight independent of shared genes. TC may be used to guide diet and predict birthweight combined with ultrasound and other indicators.